2019
DOI: 10.7554/elife.51662
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviral lytic gene functions render the viral genome susceptible to novel editing by CRISPR/Cas9

Abstract: Herpes simplex virus (HSV) establishes lifelong latent infection and can cause serious human disease, but current antiviral therapies target lytic but not latent infection. We screened for sgRNAs that cleave HSV-1 DNA sequences efficiently in vitro and used these sgRNAs to observe the first editing of quiescent HSV-1 DNA. The sgRNAs targeted lytic replicating viral DNA genomes more efficiently than quiescent genomes, consistent with the open structure of lytic chromatin. Editing of latent genomes caused short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 72 publications
4
40
1
Order By: Relevance
“…One limitation to our study is that we cannot distinguish whether the observed reduction in de novo production of viral genomes resulted from a reduction in the number of reactivation events, or instead from a decrease in virus production after a reactivation event has initiated. Our previous results suggest that newly synthesized HSV genomes are efficiently targeted by nucleases 13 , while results from our group and others demonstrate that chromatin modification of latent HSV can reduce the efficacy of gene editing 13,20,25,36 . This has important implications for the ultimate embodiment of gene editing for HSV, as it will determine whether sustained long-term expression of nuclease (as achieved using AAV vectors 22 ) is required for therapeutic benefit, or whether alternative transient delivery approaches might be sufficient.…”
Section: Discussionmentioning
confidence: 90%
“…One limitation to our study is that we cannot distinguish whether the observed reduction in de novo production of viral genomes resulted from a reduction in the number of reactivation events, or instead from a decrease in virus production after a reactivation event has initiated. Our previous results suggest that newly synthesized HSV genomes are efficiently targeted by nucleases 13 , while results from our group and others demonstrate that chromatin modification of latent HSV can reduce the efficacy of gene editing 13,20,25,36 . This has important implications for the ultimate embodiment of gene editing for HSV, as it will determine whether sustained long-term expression of nuclease (as achieved using AAV vectors 22 ) is required for therapeutic benefit, or whether alternative transient delivery approaches might be sufficient.…”
Section: Discussionmentioning
confidence: 90%
“…By using different cell models, these screens identified involvement of the cellular gene products MCLI and XPOI in KSHV-related tumorigenesis, as well as host-dependency factors that are critical for EBV-transformed B cells (33)(34)(35). In addition, direct manipulation of several herpesvirus genomes using the CRISPR-Cas9 platform was reported (7,32,(36)(37)(38). Furthermore, the effectiveness of CRISPR-Cas9 in eliminating latent EBV episomes in cell culture, by targeting key factors for latent genome replication, has been described (36,39).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of scAAV2-LAT-targeting ribozyme in the eyes of rabbits with latent HSV-1 infection blocked viral reactivation in more than 60% of the infected animals [ 80 ]. Furthermore, in recent years, multiple studies have demonstrated that the lytic and quiescent HSV genome can be targeted using the CRISPR-Cas9 system in vitro [ 81 , 82 , 83 ]. It will be interesting to see if these effects can be recapitulated through in vivo studies.…”
Section: Corneal Disordersmentioning
confidence: 99%